Смысл жизненного успеха: социально-культурологический контекст - Бевзенко, Л. (Социология: теория, методы, маркетинг, 2000)
Crucial social and cultural transformations, already realized and still realizing inpost-communist countries, cause serious transformations in personal semantic fields, sense mediums that are like lenses, through which people see their social world and construct their social relations. Individual success is a significant factor determining peopleís social life, their plans and expectations. There have been discussed social and cultural determinants of individual success formula. Semantic spaces of tradition, modern, post-modern and post-communist culture are regarded as basic cultural spaces being summed in personal result semantics.